The Effects of Puberty Blocking Treatment (Gonadotropin Releasing Hormone agonist) on Reproductive Function in Young Female Rats - Jones, Brandon; Hydock, David (Archives of Clinical and Biomedical Research, 2025)
This study investigated the effects of puberty blocking treatment on reproductive morphology and function in young female rats. Reproductive recovery of the ovaries and uteri of peri-pubescent female rats were examined by comparing H&E-stained sections. In addition to reproductive function recovery, after drug withdrawal. Four-week old peri-pubescent female Sprague Dawley rats (n=32) were given daily injections of the gonadotropin releasing hormone agonist, triptorelin or saline. After four weeks of treatment a group of rats were euthanized, and the uterus and ovaries were removed for H&E staining. Additional rats were taken off the treatment for 4 weeks to examine recovery. The final group was taken off puberty blocking treatment and housed with fertile males. Puberty blocking treatment led to a reduction in the mass of uteri and ovaries which recovered after 4-weeks withdrawal. The ovaries of the treatment group exhibited a disruption in follicle development and corpora lutea health which recuperated after 4-weeks of withdrawal. No significant difference in pregnancy rate was detected; however, both the number of days until pregnancy detection and number of days until giving birth were considerably longer in puberty blocked rats following withdrawal. The number of pups per litter was also significantly reduced by drug treatment but no abnormalities were observed in the pups. Young female rats treated with a puberty blocker had significantly delayed development of the reproductive organs, which recovered after 4 weeks of drug withdrawal. A minor disruption in reproductive function was detected immediately following drug withdrawal.